Climate Change Adaptation Constraints among Paddy Growing Farmers in Kalyana-Karnataka Region of Karnataka State - Shanabhoga, M. B.; Krishnamurthy, B.; Suresha, S. V.; Dechamma, Shivani; Kumar, R. Vinay (Indian Journal of Extension Education, 2023)
To mitigate and cope with changing climate, adaptation strategies are essential. However, farmers are facing several constraints while adapting to the changing climate. The study was conducted during 2018-19 in three major paddy growing districts of Kalyana Karnataka region of Karnataka state with 90 respondents. The Rank Based Quotient (RBQ) approach was used to assemble, tabulate, and evaluate the data. The farmers expressed the absence of a location-specific climate forecast and they couldn’t able to rely on available climate forecasts. In addition, farmers opined about the non-availability of critical inputs and fair prices for their produce. It suggested the farmers of the study region should be provided with updated and reliable information on climate change as this could help in improving their awareness on changing climate. The improvement of field extension connectivity and timely assistance to the farmers are required for better utilization of resources and adoption of climate-related strategic innovations.
Keywords: Climate change; Constraint; Suggestion; Adaptation strategy; Paddy grower